Obesity, Central Fat Patterning, and Their Metabolic Correlates among the Inuit of the Central Canadian Arctic ... - Young, T. Kue (University of Alberta Library, 1996)
"I report on the occurrence and metabolic correlates of obesity among the Inuit (Eskimos) of the central Canadian Arctic using data from the Keewatin Health Assessment Study conducted during 1990 and 1991 in eight Inuit communities in the Northwest Territories (n = 434, adults aged 18 years and older). Data from the 1990 Manitoba Heart Health Survey among 2200 predominantly white residents of the province of Manitoba were used for comparison. Judging by body mass index and two skinfold thicknesses, obesity among the Inuit is as prevalent as it is in the general North American population." (as cited in abstract) ...